Stigma Experiences, Mental Health, Perceived Parenting Competence, and Parent–Child Relationships Among Lesbian, Gay, and Heterosexual Adoptive Parents in the United States - Farr, Rachel H.; Vázquez, Cassandra P. (Frontiers in Psychology, 2020)
Adoptive parents often face stigma related to “nontraditional” family structures. Lesbian and gay (LG) adoptive parents often face additional stigmatization based on sexual identity, which in turn may negatively affect parents’ mental health. Despite controversy about LG parenting, research demonstrates that family processes are more strongly associated with individual outcomes than family structure. Thus, family systems and minority stress theories provided our conceptual foundation in examining how adoptive LG parents’ stigma experiences were associated with mental health, parenting competence, and parent-child relationships. Participating families (N = 106; n = 56 LG parent families) were originally recruited from five United States domestic private infant adoption agencies and completed two waves of data collection (W1, W2; 91% retention) when children were preschool-age (Mage = 3.01 years) and school-age (Mage = 8.36 years), respectively. Data for the current study are largely drawn from W2. Via Qualtrics, parents completed assessments of mental health symptoms, adoption stigma, and perceived childcare competence. LG parents also reported on their experiences of homonegative microaggressions, and children responded to a measure about their relationships with parents. No significant differences emerged as a function of parental sexual orientation and gender except that lesbian mothers, heterosexual mothers, and gay fathers all reported higher parenting competence than heterosexual fathers. Although parents’ mental health did not significantly predict parent-child relationship quality, parents’ perceived competence and LG parents’ current homonegative microaggression experiences did (e.g., greater competence, greater closeness; more microaggressions, lower closeness). Consistent with our conceptual framework, our results – derived from parent and child reports – demonstrate that although adoptive and LG parent families experience stigma, family processes (rather than structure) are most associated with individual outcomes. Researchers, policymakers, and practitioners should work together to employ identity-affirming practices to reduce stigma and support adoptive family functioning and well-being.